Breast Tuberculosis in Southeast Turkey: Report of 27 Cases - Tanrikulu, Abdullah C. (S. Karger GmbH, 2010)
BACKGROUND: Breast tuberculosis (TB) is a very rare form of TB. Case series on breast TB are scarce. PATIENTS AND METHODS: The patients with breast TB treated between 2004 and 2008 at our hospital were retrospectively investigated. RESULTS: All patients were female (mean age 31.5 ± 8.4 years). All but 1 patient were new cases. Patients presented with swelling of the breast (48.1%), mass and fluctuation (each, 40.7%), and breast pain (18.5%). The mean treatment duration was significantly shorter in 14 patients who received directly observed therapy (DOT) compared with those (n = 12) who did not (6.7 ± 1.7 months vs. 8.5 ± 1.6 months, respectively; p = 0.01). Seven patients underwent segmental mastektomy as complementary surgery. The highest rate of breast TB was seen in 2007 (37.1% compared with 14.8% between 2004 and 2006). CONCLUSIONS: Breast TB should be considered in patients with breast neoplasia, swelling, and discharge, and can be successfully treated by DOT with shorter treatment duration.